Neglected Congenital Glaucoma With Lens Coloboma. Issue 8 (August 2019) - Dhingra, Deepika; Tekchandani, Uday; Pandav, Surinder S.; Kaushik, Sushmita
Abstract : Purpose: To report a case of lens coloboma in a case of neglected primary congenital glaucoma. Materials and Methods: A 5-year-old boy was brought by the parents with complaints of diminution of vision in both eyes noticed for 8 months. There was a history of enlargement of eyes since 1 year of age. Results: Clinical examination revealed bilateral large eyes with limbal stretching and Haab striae and lens coloboma in the right eye. Dilated examination revealed scalloped border of the crystalline lens superotemporally with broken zonules and lens coloboma in inferotemporal quadrant with absent zonules. There was advanced optic nerve head cupping in both eyes. This lens coloboma is likely an acquired condition due to extensive stretching of the lens and zonules secondary to globe enlargement in neglected buphthalmos. Conclusion: A neglected case of congenital glaucoma can lead to lens subluxation along with lens coloboma.